2015
DOI: 10.4238/2015.august.10.17
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor 1 PvuII and XbaI polymorphisms and susceptibility to Alzheimer’s disease: a meta-analysis

Abstract: ABSTRACT. The aim of this study was to explore whether estrogen receptor 1 (ESR1) PvuII and XbaI polymorphisms are associated with susceptibility to Alzheimer's disease (AD). We conducted a metaanalysis of the associations between AD and ESR1 PvuII and XbaI polymorphisms as well as haplotypes of the ESR1 PvuII and XbaI polymorphisms. A total of 1359 patients and 1387 controls from 9 studies on the ESR1 PvuII polymorphism and 1525 patients and 1575 controls from 8 studies on the ESR1 XbaI polymorphism were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
(53 reference statements)
1
7
1
Order By: Relevance
“…In the present study, the ERα PvuII pp genotype was associated with higher OR for dementia. These findings corroborate other studies that found that polymorphism in ER alfa is associated with an increased risk of AD in Caucasian [13], Chinese [14], Japanese [15], UK [16] and European [17] populations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the ERα PvuII pp genotype was associated with higher OR for dementia. These findings corroborate other studies that found that polymorphism in ER alfa is associated with an increased risk of AD in Caucasian [13], Chinese [14], Japanese [15], UK [16] and European [17] populations.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the pp genotype for the ERα PvuII variant remained significant for female, as observed by Porrello et al in an Italian female Alzheimer population [21]. These data are contrary to those found by [15], where the association was observed only in males [15]. However, the results for cognitive functions depends on which Xba1 polymorphism the woman carries [12].…”
Section: Discussioncontrasting
confidence: 79%
“…DNA methylation at the ERα promoter region can suppress the gene expression by recruiting various binding proteins, which interfere with the basal transcriptional machinery or by recruiting histone deacetylases that can condense the chromatin and thereby suppress the overall gene transcription. 27 It has been shown that ERα PvuII polymorphism was related to AD 28 ; thus, this gene was selected as for the present study. Westberry et al reported that the expression of ERα mRNA remains low when the methylated promoters of the ERα gene transpired in the female adult cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have addressed the problem of the effect of ERα Xba1 and PvuII polymorphisms on the development of dementia on the AD background. Lee, in meta-analysis of studies involving approximately 6000 people (males and females), investigated this effect, reporting a relationship between CC and CT PvuII polymorphism and the development of AD in males, without any effect on the development of AD in females [ 49 ].…”
Section: Discussionmentioning
confidence: 99%